Community Empowerment through the Application of Technology to Increase Copra Production for Farmer Groups in Saweli Village, Taniwel, West Seram - Mimi Salmawati; Nelson Gaspersz; Priska Marisa Pattiasina (Pascasarjana Universitas Mataram, 2026)
West Seram Regency has a coconut plantation area of 8,326.10 hectares, with a total production of 7,390.5 tons and an average productivity of 0.89 tons per hectare. Nearly all parts of the coconut plant can be utilized, including the trunk, leaves, fruit, husk, and shell. The use of mature coconuts for copra production is one of the ways to increase the income of coastal communities, particularly in Saweli Village, located in West Seram Regency. However, copra production in Saweli Village, which is generally carried out using traditional or home-industry methods, has not yet reached optimal results in terms of production time and output quantity. One of the main challenges faced by the community is the lengthy process of removing the coconut husk and shell during copra production. The current pre-processing stage remains conventional, as coconuts are peeled manually using traditional tools. Therefore, through this Community Empowerment Program (PMS), we aim to introduce transformative learning to help develop and empower the local community, particularly in Saweli Village, Taniwel District, West Seram Regency, Maluku. This initiative focuses on supporting small-scale entrepreneurs whose production processes have not yet met market standards.